The R148.3 Gene Modulates Caenorhabditis elegans Lifespan and Fat Metabolism. Issue 8 (1st August 2017) - Roy-Bellavance, Catherine; Grants, Jennifer M; Miard, Stéphanie; Lee, Kayoung; Rondeau, Évelyne; Guillemette, Chantal; Simard, Martin J; Taubert, Stefan; Picard, Frédéric
Abstract: Despite many advances, the molecular links between energy metabolism and longevity are not well understood. Here, we have used the nematode model Caenorhabditis elegans to study the role of the yet-uncharacterized gene R148.3 in fat accumulation and lifespan. In wild-type worms, a R148.3 p ::GFP reporter showed enhanced expression throughout life in the pharynx, in neurons, and in muscles. Functionally, a protein fusing a predicted 22 amino acid N-terminal signal sequence (SS) of R148.3 to mCherry displayed robust accumulation in coelomyocytes, indicating that R148.3 is a secreted protein. Systematic depletion of R148.3 by RNA interference (RNAi) at L1 but not at young-adult stage enhanced triglyceride accumulation, which was associated with increased food uptake and lower expression of genes involved in lipid oxidation. However, RNAi of R148.3 at both L1 and young-adult stages robustly diminished mean and maximal lifespan of wild-type worms, and also abolished the long-lived phenotypes of eat-2 and daf-2 /InsR mutants. Based on these data, we propose that R148.3 is an SS that modulates fat mass and longevity in an independent manner.